2023
DOI: 10.1039/d3tc02716c
|View full text |Cite
|
Sign up to set email alerts
|

Moderate temperature sulfurization and selenization of highly stable metal oxides: an opportunity for chalcogenide perovskites

Shubhanshu Agarwal,
Jonathan W. Turnley,
Apurva A. Pradhan
et al.

Abstract: Oxide perovskites would provide a convenient precursor for the synthesis of chalcogenide perovskites. However, the stability of oxide perovskites means that there is no driving force for sulfurization or selenization...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…However, the Agrawal group has recently shown that the thermodynamics around the sulfurization step can be altered by heating in the presence of both HfH 2 and sulfur. 182 The sulfur initially reacts with the HfH 2 to produce HfS 3 and H 2 S. This HfS 3 then functions as a powerful oxygen trap through the formation of HfO 2 and the oxygen can be transported out of the oxide perovskite to the trap through an H 2 O/H 2 S shuttle. While a simple sulfurization is not able to convert a BaZrO 3 film into BaZrS 3 , this reconfigured sulfurization changes the thermodynamics to facilitate the conversion at 575 °C.…”
Section: Solution Processing Of Emerging Metal Chalcogenidesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Agrawal group has recently shown that the thermodynamics around the sulfurization step can be altered by heating in the presence of both HfH 2 and sulfur. 182 The sulfur initially reacts with the HfH 2 to produce HfS 3 and H 2 S. This HfS 3 then functions as a powerful oxygen trap through the formation of HfO 2 and the oxygen can be transported out of the oxide perovskite to the trap through an H 2 O/H 2 S shuttle. While a simple sulfurization is not able to convert a BaZrO 3 film into BaZrS 3 , this reconfigured sulfurization changes the thermodynamics to facilitate the conversion at 575 °C.…”
Section: Solution Processing Of Emerging Metal Chalcogenidesmentioning
confidence: 99%
“…This process then enables the use of solution processed oxide perovskites as precursors for chalcogenide perovskite thin films with moderate temperature processing. 182…”
Section: Solution Processing Of Emerging Metal Chalcogenidesmentioning
confidence: 99%